Ethnobotany of Plants in Tagkawayan: Input for Information Communication Media on Medicinal Uses of Plants (Philippine Journal of Agricultural Economics, 2017)
In the Philippine countryside, where barrio folks are closely entwined with their natural environment, their close contact especially to the adjoin dipterocarp forests makes them more knowledgeable on the different uses of plants. This study focuses on the exploration of the traditional knowledge of plants more specifically on its medicinal uses. An enhanced and adapted semi structure interview guide was employed and a qualitative approach was incorporated in data gathering. The study recorded a total of 136 plant species of which 52% (81 species) were of medicinal uses, the foremost plant part used were the leaves (58%), route of administration was internal application (67%) and the most commonly method of preparation is boiling (58%). The dosage frequently given was 3x a day. Results showed a rich diversity of plant species in Tagkawayan and the barrio folks are knowledgeable on the traditional uses of plants, but this knowledge were not yet explored because these are trapped among older generation that are transferred through verbal means. Development of a reading material will be of great help for preservation and information dissemination of these beneficial uses of plants.  The use of leaves is an indication that the biodiversity in the place is ensured and continued reliance on the use of herbal plant showed that plants could be a better alternative for synthetic drugs in treatment of common diseases.